Public Service Innovation at Tomohon City Population and Civil Registration Office - Posuma, Sweetly N.; Tumbel, Goinpeace H.; Tarore, Steven (Technium Social Sciences Journal, 2024)
This research aims to analyze: Public Service Innovations at the Tomohon City Population and Civil Registration Service. This research approach uses a descriptive qualitative approach, with 10 predetermined informants using data collection techniques, namely observation, interviews, and documentation with data analysis techniques through data reduction, data presentation, and drawing verification conclusions. The results of this research show that the Public Service Innovation, namely the Tomohon HEBAT Population Administration Online Service System (SLOATH) at the Tomohon City Population and Civil Registration Service, is quite good as seen from the 5 (five) characteristics/aspects of innovation which are the sub-focus of this research, namely Relatif Advantage, Compatibility, Complexity, Triability, and Observability. It's just that regarding the timeliness of employee responses to the process of using applications from the community which is not yet very responsive, the lack of human resources and infrastructure provided by the Department is quite an obstacle in implementing this innovation, so this innovation cannot be said to be effective and efficient in providing services to the community. Suggestions that can be given should be from the government, in this case the Department of Education and Civil Registration, to add human resources and infrastructure so that in serving the community there will no longer be delays that make the community wait to get a response when using the application.